Aretusa: continuity, rupture and space for intervention (1944–46). Issue 1 (1st January 2016) - La Penna, Daniela
Abstract: This article focuses on the cultural activity of Aretusa (1944–46), a journal that was deeply connected to the inner circle of philosopher and politician Benedetto Croce (1866–1952). The article analyses the role played by periodical editors Francesco Flora (1891–1962) and Carlo Muscetta (1912–2004) in shaping the mission and direction of this journal. By drawing on Pierre Bourdieu's theory of habitus, and the notion of hysteresis in particular, this study details the factors influencing the aesthetic dispositions, political positioning and the wider impact of historical circumstances on the cultural practice of each editor while at the helm of the review.